2016
DOI: 10.1002/1873-3468.12191
|View full text |Cite
|
Sign up to set email alerts
|

LYR3, a high‐affinity LCO‐binding protein of Medicago truncatula, interacts with LYK3, a key symbiotic receptor

Abstract: Edited by Julian Schroeder LYR3, LYK3, and NFP are lysin motif-containing receptor-like kinases (LysM-RLKs) from Medicago truncatula, involved in perception of symbiotic lipo-chitooligosaccharide (LCO) signals. Here, we show that LYR3, a highaffinity LCO-binding protein, physically interacts with LYK3, a key player regulating symbiotic interactions. In vitro, LYR3 is phosphorylated by the active kinase domain of LYK3. Fluorescence lifetime imaging/F€ orster resonance energy transfer (FLIM/FRET) experiments in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 49 publications
1
57
0
Order By: Relevance
“…PCR products were purified on agarose gel with Wizard SV Gel and PCR Clean-Up System (Promega) and were cloned in a pBIN19 Gateway expression vector pBin19-35S-GW-YFP (Froidure et al, 2010), (kindly provided by Susana Rivas, LIPM Toulouse) in order to create fusion proteins with YFP in N-terminal part of the protein; the effector domain of the protein is free to interact with other molecules and potentially fully functional. CRN37 coding sequence deleted from its first 19 amino acids was fused to a peptide tag GFP under the control of 35S promoter and cloned in one step in the expression vector pCAMBIA-CR1 (Fliegmann et al, 2016) using the cloning method “Golden gate” (Engler et al, 2008, 2009). pCAMBIA-CR1 vector containing GFP under the control of 35S promoter was used as positive control for PhCRN37 transient expression experiments.…”
Section: Methodsmentioning
confidence: 99%
“…PCR products were purified on agarose gel with Wizard SV Gel and PCR Clean-Up System (Promega) and were cloned in a pBIN19 Gateway expression vector pBin19-35S-GW-YFP (Froidure et al, 2010), (kindly provided by Susana Rivas, LIPM Toulouse) in order to create fusion proteins with YFP in N-terminal part of the protein; the effector domain of the protein is free to interact with other molecules and potentially fully functional. CRN37 coding sequence deleted from its first 19 amino acids was fused to a peptide tag GFP under the control of 35S promoter and cloned in one step in the expression vector pCAMBIA-CR1 (Fliegmann et al, 2016) using the cloning method “Golden gate” (Engler et al, 2008, 2009). pCAMBIA-CR1 vector containing GFP under the control of 35S promoter was used as positive control for PhCRN37 transient expression experiments.…”
Section: Methodsmentioning
confidence: 99%
“…LysM receptors are a subclass of membrane-bound plant pattern recognition proteins that have multiple repeats of the LysM domain in the extracellular portion of the protein attached to a cytoplasmic kinase signaling domain. Early characterization of these proteins found that certain LysM receptor kinases, namely NFR1 and NFR5, have a role in perceiving secreted lipochitooligosaccharides (LCOs; called 'Nod factors') from rhizobial bacteria (Amor et al, 2003;Limpens et al, 2003;Madsen et al, 2003;Malkov et al, 2016), and in inducing the initial signaling response by the plant necessary to establish the formation of these mutualistic root nodules Fliegmann et al, 2016). AM fungi also produce LCOs that are perceived by plant LysM receptors and induce a signaling cascade within the plant that fosters symbiosis (Maillet et al, 2011;Malkov et al, 2016;Carotenuto et al, 2017).…”
Section: What Might Influence Differential Plant Responses To Differementioning
confidence: 99%
“…The transcriptional reporter pMtBG2:GUS, pNIN:GUS, pERN1: GUS, the pEXPA:PV cd (PV cd , parvalbumin mutated in EF hand motif, Addgene, reference Plasmid #16345):NLS:CFP [54], pEXPA:YFP, pEXPA:mCherry-ER and the pERN1:MtBG2 RNAi constructs were obtained by Golden-Gate cloning in pCambiaCR1 derived vectors [55]. DNA fragments corresponding to 1400 bp or 2100 bp upstream the ATG of NIN, 1705 bp upstream the ATG of MtBG2 (Medtr3g083580), 2200 bp upstream the ATG of ERN1, 401 bp of upstream EXPA sequences [30] were amplified by PCR, cloned in pbluescript vectors and sequenced before concatenated using Golden-Gate assembly reactions [55]. The pERN1: cals3m, pMtBG2:cals3m and pANN1:cals3m constructs were generated by combining restriction enzyme and gateway cloning.…”
Section: Dna Constructsmentioning
confidence: 99%